2019
DOI: 10.3390/cancers12010049
|View full text |Cite
|
Sign up to set email alerts
|

Dose Intensity/Body Surface Area Ratio is a Novel Marker Useful for Predicting Response to Lenvatinib against Hepatocellular Carcinoma

Abstract: Lenvatinib was recently approved as a novel first-line molecular targeted agent (MTA) for treating hepatocellular carcinoma (HCC). The importance of relative dose intensity (RDI) has been shown in the treatment of various types of cancers. However, RDI may not accurately reflect the treatment intensity of lenvatinib, as it is the first oral MTA where the dose is based on the patient's weight. We aimed to evaluate the utility of 2M-DBR (the delivered dose intensity/body surface area ratio at 60 days) by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 33 publications
3
31
3
Order By: Relevance
“…In the present study, median PFS was 5.0 months, which was shorter than that in the phase 3 REFLECT trial, revealing median PFS was 7.4 months in the overall population and 7.2 months in the Japanese subset [18]. However, in real-world settings, median PFS ranging from 4.4 to 5.4 months has been reported, consistent with our results [19,20]. This may be explained by more patients in real-world settings being aged and having low ECOG-PS score and Child-Pugh score compared with the clinical trial.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, median PFS was 5.0 months, which was shorter than that in the phase 3 REFLECT trial, revealing median PFS was 7.4 months in the overall population and 7.2 months in the Japanese subset [18]. However, in real-world settings, median PFS ranging from 4.4 to 5.4 months has been reported, consistent with our results [19,20]. This may be explained by more patients in real-world settings being aged and having low ECOG-PS score and Child-Pugh score compared with the clinical trial.…”
Section: Discussionsupporting
confidence: 88%
“…This indicates that maintaining a higher dose is important to maintain a higher Cmax. Maintaining more than 70% RDI in lenvatinib has been reported to be an independent factor for a better therapeutic response and better PFS [32]. In the weekends-off protocol, the RDI can be maintained at 71.4%, and this might have, in part, accounted for the 50% improvement of a therapeutic effect in our study.…”
Section: Discussionsupporting
confidence: 49%
“…However, among the patients who required dose reduction due to AEs, a therapeutic response has also recovered again in 61.5% of the patients when the weekends-off administration was implemented using the original dose of lenvatinib. A recent study showed that Cmax and relative dose intensity (RDI) are important in the therapeutic effect of lenvatinib [32][33][34]. Ikeda et al and Tamai et al reported that the Cmax of lenvatinib is reduced by nearly 50% and the AUC is decreased by 55% when the dose is reduced from 12 mg to 8 mg [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…According to the clinical practice guidelines on the management of HCC (3,4), both sorafenib and lenvatinib were recommended as the first-line systemic therapy options for patients with advanced stage HCC. Because the REFLECT trial reported superior antitumor response and progression-free survival (PFS) with lenvatinib over sorafenib (5,6), lenvatinib has been increasingly selected as the first-line therapy in clinical practice (7)(8)(9)(10). However, the outcomes of ramucirumab treatment after lenvatinib failure are unknown, because the REACH-2 trial was conducted on patients with prior sorafenib intake (1).…”
mentioning
confidence: 99%